PENGARUH MOTIVASI DAN STRES KERJA TERHADAP KINERJA PEGAWAI - Hotiana, Nila; Febriansyah, Febriansyah (Economic Faculty, Attahiriyah Islamic University, 2018)
This research was aimed for knowing the influence between motivation and work stress against the employees’ performance of staffing and Organization General Bureau, staffing and Organization the Ministry of Tourism. This research used a quantitative approach through survey to 40 employees. All population is used as sample. Hypothesis test (t test) result that shows that the variable compensation affect significantly to these performance proved by t value about 2.693 which is more than t table. But the variable of work stress do not affect significantly with t value about 1.994 which is less than t table. The conclusion of this research is motivation is the most dominant variable over the performance of the employees. This means that increasing performance of the emplooyees can be seen from the way the institutions provide motivation to employees. Keywords: motivation, work stress, employee’s performance